Industrializing precast productions: Adaptive modularized constructions made in a flux. Issue 3 (29th June 2021) - Mark, Peter; Lanza, Gisela; Lordick, Daniel; Albers, Albert; König, Markus; Borrmann, Andre; Stempniewski, Lothar; Forman, Patrick; Frey, Alex Maximilian; Renz, Robert; Manny, Agemar; Stindt, Jan
Abstract: Building in heavy rain is seldom beneficial, but common practice on site. It promotes inaccuracies and impairs the use of modern but sensible high‐performance materials and costs time, since disruption in construction frequently causes complicated returns to the planning process. Nevertheless, a handcrafted production process is still considered the one and only alternative since all buildings are unique and thus must be manually constructed on site. Indeed? The priority program entitled "Adaptive modularized constructions made in a flux" funded by the German Research Foundation follows a completely new approach. Buildings are divided into similar modular precast concrete elements, prefabricated in flow production, quality‐assured, and just‐in‐time assembled on site. Comparable to puzzles with many pieces, the uniqueness of the structure is maintained. The motto is: "Individuality on a large scale‐similarity on a small scale". The contribution presents approaches of modularization, production concepts, and linking digital models. Serial, stationary prefabrication enables short production times and resource‐efficient modules that are assembled to load‐bearing structures with low geometrical deviations. Stringent digitalization ensures high quality of all intermediate steps. These comprise fabrication, assembly, and the whole service life of the structure. The result is a lean production process.